Observations on the Regulation of Tourism in Accordance with the Constitution of the Republic of Indonesia 1945 and Relevant Legislation - Sunarti, Sri; Hatibie, Irma Kharisma; Husain, Yeristiawati (Universitas Negeri Gorontalo, 2024)
Tourism plays a crucial role in economic development and the welfare of society. It is essential to note that tourism development must consider the legal regulatory aspects, particularly in the formulation of laws and regulations. Therefore, an assessment of the regulations governing tourism is necessary to ensure the harmonization and synchronization of the tourism sector itself. The objective of this study is to examine and analyze the regulatory aspects of tourism in accordance with the Constitution and prevailing laws and regulations. This research is normative, using legal materials as its primary source. The research employs a legislative approach, a conceptual approach, and a case-based approach. The findings of the study indicate that the assessment of tourism regulations in alignment with the Constitution and existing laws can be carried out in two main ways: first, through the systematization of tourism-related regulations, and second, by evaluating existing tourism regulations, starting from the Constitution itself, followed by the laws, government regulations, ministerial regulations, and regional regulations at both provincial and municipal levels. Additionally, the assessment serves as the most effective means of maintaining the harmony and synchronization of the laws and regulations governing tourism.